Joyful recollections of trauma - Scheer, Paul, 1976- (HarperOne, an imprint of HarperCollinsPublishers, 2024)
"From award-winning actor and comedian Paul Scheer, a candid and hilarious memoir-in-essays on coming to terms with childhood trauma and finding the joy in embracing your authentic self"--